Soluble CD163 Concentration in Chronic Lymphocytic Leukemia and its Correlation with Prognostic Parameters - Mouayad Jawad, Marwa; Mohammed Baqir Al-Bayaa , Israa (Hammurabi Journal of Medical Sciences, 2025)
Background: Chronic Lymphocytic Leukemia (CLL) is a clonal malignancy of mature B-lymphocytes characterized by significant clinical heterogeneity. Soluble CD163 (sCD163), a monocyte/macrophage-specific scavenger receptor, has been associated with disease severity and prognosis in several malignancies. However, its role in CLL remains unclear. While traditional staging systems like Rai and Binet remain foundational, emerging biomarkers offer enhanced prognostic precision. Among these, CD163, β2-Microglobulin (β2MG), and leukocyte-associated immunoglobulin-like receptor-1 (LAIR-1) have demonstrated clinical relevance. Objectives: To evaluate plasma levels of soluble CD163 at diagnosis in patients with CLL in comparison to healthy controls, correlate sCD163 levels with clinical staging, hematological parameters, and other prognostic parameters such as plasma B2MG and LAIR-1 expression. Materials and methods: This is A cross-sectional study was conducted over six months (December 2023 – May 2024), involving 88 individuals. Group I included 68 newly diagnosed CLL patients, and Group II consisted of 20 healthy controls. Diagnosis was confirmed via peripheral blood morphology and immunophenotyping using 8-color flow cytometry (BD FACS Canto II). Data collected included demographic and clinical features, hematological profiles, LAIR-1 expression, B2MG levels, and Binet clinical stage. Results: Significant difference for mean concentration of both soluble CD163 and B2MG between patients and control group with p value (0.022,0.003) respectively. No significant correlation was found between sCD163 and B2MG, hemoglobin levels, platelet counts, absolute lymphocyte count, smudge cell%, or LAIR-1 expression. Furthermore, sCD163 levels did not significantly differ across Binet stages (p = 0.704). Conclusion: Plasma CD163 levels are significantly reduced in CLL patients compared to healthy individuals, suggesting a potentially different role of macrophage-derived markers in CLL compared to other lymphomas. However, its lack of association with disease stage or other prognostic markers indicates limited utility as a standalone prognostic biomarker in CLL.